2011
DOI: 10.1186/1472-6963-11-239
|View full text |Cite
|
Sign up to set email alerts
|

Implementing knowledge into practice for improved neonatal survival; a cluster-randomised, community-based trial in Quang Ninh province, Vietnam

Abstract: BackgroundGlobally, almost 4 million newborns die during the first 4 weeks of life every year. By increased use of evidence-based knowledge in the healthcare system a large proportion of these neonatal deaths could be prevented. But there is a severe lack of knowledge on effective methods for successful implementation of evidence into practice, particularly in low- and middle-income countries. Recent studies have demonstrated promising results with increased survival among both mothers and newborns using commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 36 publications
(47 reference statements)
0
46
0
Order By: Relevance
“…19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 Among these, 77 references were excluded 19, 20, 21, 22, 23, 24, 25, 26, 27, <...>…”
Section: Resultsmentioning
confidence: 99%
“…19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 Among these, 77 references were excluded 19, 20, 21, 22, 23, 24, 25, 26, 27, <...>…”
Section: Resultsmentioning
confidence: 99%
“…Since the first PARIHS publication in 1998, the framework has been subject to evaluation, which has provided reasonable evidence for validity of its content and constructs [18-22]. Presently, the framework is also being evaluated in large-scale studies in both Europe and Vietnam [23,24]. Furthermore, the framework was recently subjected to systematic critical synthesis where authors concluded that there is empirical support for the separate cornerstones, although there is a need for rigorous prospective studies where the framework is used and evaluated [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increasing community awareness about the importance of appropriate NH care increases service demand which can have an impact on providers’ adoption of guidelines [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In China, neonatal mortality accounts for 60 % of all childhood deaths [13] while in Vietnam, neonatal mortality comprises nearly three-quarters of all infant deaths [11]. Higher rates of neonatal mortality exist in poorer and remote rural areas of both countries.…”
Section: Introductionmentioning
confidence: 99%